Treadmill exercise training improves the high-fat diet-induced behavioral changes in the male rats - Bulmus, Ozgur; Ercan, Zubeyde; Kacar, Emine; Serhatlioglu, Ihsan; Yasar, Abdullah; Kelestimur, Haluk (Springer Heidelberg, 2022)
The purpose of this study was to investigate the effects of treadmill exercise training on obesity-induced behavioral changes in high-fat diet (HFD)-induced male rats. In this study, 40 male Sprague-Dawley rats were divided into 4 groups after they were weaned: Control (C), Exercise (E), Obese (O) and Obese + Exercise (O + E). For the obesity model % 60 high-fat diet were applied. After obesity was induced, rats were either moderate aerobic exercise (treadmill running) trained or left untrained. Different tasks to assess spatial learning and memory (Morris water maze test (MWMT)), depressive-like behavior (forced swimming test(FST), tail suspension test (TST) and anxiety-like behavior (light-dark test (LDT) and open field test (OFT)) were conducted. Exercise caused a significant reduction in duration of immobility in the O group in FST and the decrease in immobility in the O + E rats in TST. The O + E rats demonstrated a significant increase in the time spent in the light box as compared to the O group in the LDT. The O + E rats did not show any behavioral alterations as compared to all the other groups in the OFT. In the O + E group, there was a significant increase in the time spent in the target quadrant compared to the O group in the MWMT. Our results support that treadmill exercise could improve cognitive, depressive-like, anxiety-like behavioral changes in the HFD-induced obese rats.
Keywords: Treadmill exercise; Obesity; Behavior; High-fat diet; Rat